2015
DOI: 10.1186/s13011-015-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of public support toward federal funding for harm reduction strategies

Abstract: BackgroundHistorically, US federal policy has not supported harm reduction interventions, such as safe injection facilities (SIFs) and needle and syringe programs (NSPs), which can reduce the burden associated with injection drug use. Given recent increases in abuse of both legal and illegal opioids, there has been a renewed debate about effective ways to address this problem. The current study (1) assessed participants’ support for SIFs and NSPs, and (2) evaluated several demographic factors (e.g., age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
5
35
2
2
Order By: Relevance
“…Although preliminary, these results raise important questions for future investigations about the value of targeting implicit addiction stigma to promote better care for PWIDs and others coping with SUDs. In light of research suggesting that moralistic, punitive beliefs are related to lower support for funding of healthcare services for SUDs (Kulesza et al, 2015; MacCoun, 2013), effective strategies to address implicit beliefs that PWIDs (especially Latino/a) are more deserving of punishment than help may one day improve access to help for this underserved population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although preliminary, these results raise important questions for future investigations about the value of targeting implicit addiction stigma to promote better care for PWIDs and others coping with SUDs. In light of research suggesting that moralistic, punitive beliefs are related to lower support for funding of healthcare services for SUDs (Kulesza et al, 2015; MacCoun, 2013), effective strategies to address implicit beliefs that PWIDs (especially Latino/a) are more deserving of punishment than help may one day improve access to help for this underserved population.…”
Section: Discussionmentioning
confidence: 99%
“…), among the general public (Kulesza et al, 2015; Lee and Rasinski, 2006; MacCoun, 2013; Matheson et al, 2013). Thus, moralistic and punitive views towards individuals who use drugs seem to be adversely related to availability of help services for SUDs (Kulesza et al, 2015; MacCoun, 2013). On the individual-level, persons with SUDs might decide against seeking help to avoid anticipated stigma from healthcare providers, employers, and/or neighbors (Link et al, 2001, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…While stigma towards substance use and people who use substances is well-documented (Kennedy-Hendricks et al, 2016, 2017; Kulesza et al, 2015; MacCoun, 2013; Pescosolido et al, 2010), its impact on stigmatized persons continues to be understudied and poorly understood (Corrigan et al, 2017; Kulesza et al, 2013; National Academies of Sciences, Engineering, and Medicine, 2016; Smith et al, 2016). We add to the literature by evaluating the relationship between internalized stigma and substance use problems (SUP), defined as negative consequences of substance use such as legal or financial problems (Blanchard et al, 2003).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Part Two: Literature Review The history of stigma associated with illicit drug use and PWUD continues to negatively impact the quality and availability of evidence-based harm reduction services (Kulesza, Teachman, Werntz, Gasser, & Lindgren, 2015;Pauly, 2008a;Wild, et al, 2017). The benefits of harm reduction are well documented .…”
Section: Guidelines To Destigmatize Harm Reduction Workmentioning
confidence: 99%
“…In the U.S., a 2015 study showed 81% of participants somewhat to strongly supported NSPs, and 60% somewhat to strongly supported SIFs (Kulesza et al, 2015). Two decades ago, Blendon and Younge (1998) researched American attitudes towards policies established under the war on drugs mentality.…”
Section: Public Perceptionsmentioning
confidence: 99%